Stable Carbon-Centered Radicals Based on N-Heterocyclic Carbenes - Ghadwal, Rajendra S. (Synlett, 2019)
Carbon-centered radicals and diradicaloids based on classical N-heterocyclic carbene (NHC) scaffolds are readily accessible as crystalline solids. The presence of an aryl (Ar) substituent at the C2-position is the key to the remarkable stability of these open-shell species as it provides appropriate room for the spin-density delocalization. Two catalytic as well as high-yielding protocols have been developed to install a suitable aryl group at the C2-position of NHCs. The spin-density in mono-radicals (NHCAr)• is mostly located on the parent carbene carbon (C2) atom. The bridging of two NHCs through a phenylene spacer (C6H4)n enables the isolation of various p-quinodimethane (p-QDM) derivatives, which may be considered as open-shell Kekulé diradicaloids. The diradical character of these NHC-analogues of Thiele (n = 1), Chichibabin (n = 2), and Müller (n = 3) hydrocarbons [(NHC)(C6H4)n(NHC)] can be tuned by a rational choice of the size and/or the topology of spacers. In this account, the synthesis, structure, and properties of this new class of radical hydrocarbons is presented.1 Introduction2 NHC-Monoradicals3 NHC-Diradicaloids4 Conclusion
Keywords: radical; diradical; diradicaloid; carbene; hydrocarbon; heterocycle; open-shell; paramagnetic